Effect of Antioxidants (Vitamin C and E) on Function of Testes in Albino Mice Treated With Hexavalent Chromium - Salman, R. A.; Yousif, W. H.; Taha, M. N. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
Effect of antioxidants (vitamins C and E) (500mg/kg) was studied on function of testes in albino mice treated with hexavalent chromium (1000ppm). The results showed that exposure to hexavalent chromium caused a significant decrease in body weights, without changes in weight of testes, seminal vesicles and prostate. A significant decrease was observed in the percentage of dead sperms, sperms abnormalities, diameter of seminiferous tubules and the number of leydig cells. Degenerative changes and necrosis were observed in the lumen of seminiferous tubules. Treatment of hexavalent chromium-exposed mice with vitamin C caused improvement in weights and characters of sperms and improvement of the tissue of seminiferous tubules. Treatment with vitamin E to animals exposed to hexavalent chromium showed improvements in body weights, seminal vesicles weight, the percentages of sperm abnormalities dead sperms and the total sperms number. An increase was demonstrated in the percentage of live sperms, and the diameter of the seminiferous tubules and leydig cells .  The histological structure of the seminiferous tubules returned to the normal     state.